Defaults in charitable giving - Jonathan F. Schulz; Petra Thiemann; Christian Thöni (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
In an experimental setup we investigate the effect of defaults on charitable giving. In the treatment group, subjects can either specify a charity of their choice, or select one from a default list of five wellknown charities; in the control group we do not provide the list. In a sample of 869 subjects we find that offering a list of default charities doubles both the fraction of donors and the aggregate amount of donations. These findings point to the importance of psychological factors like affective reactions in donation decisions.
Keywords: C93; D64; H41; L3; 330; charitable giving; defaults; donation; affective reactions